APLIKASI SCREENING OF REPRODUCTIVE HEALTH (SHE) DALAM UPAYA PENINGKATAN KESEHATAN REPRODUKSI WANITA - Azizatul Hamidiyah; Muhasshanah Muhasshanah (JOMIS (Journal of Midwifery Science), 2020)
Anemia, vaginal discharge, menstrual disorders, dysmenorrhea are some of the reproductive health problems experienced by women both on a mild to severe scale. And some can be fatal to death. However, reproductive health problems are not balanced with the level of knowledge by women about the problems experienced. So it is not uncommon, the women only realize after the situation is getting worse. Therefore an information system is needed that can help women early detect reproductive health problems experienced by women, one of them with an expert system. The purpose of this study was to create a Screening of Reproductive Health (SHE) application in an effort to improve Women's Reproductive Health. The research method used the expert system design method by coding and decision tables, making decision trees and flowcharts. conduct stages of data collection in the form of problem domain discussions with experts, literature studies, decision tree discussions with experts and trials to 30 respondents. The results showed that the expert system had been made according to the design and had produced the solutions needed in reproducing reproductive health along with suggestions and recommendations from the diagnosis results.